PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA ANGGOTA KEPOLISIAN - Ratnasari, Sri Langgeng (Journal of Innovation in Business and Economics, 2010)
This research aims to know the influence of variable of organizational citizenship behavior (OCB) consist of compliance, participation, and loyalty simultaneously and partially to personnel of Poltabes Barelang (Batam, Rempang dan Galang) performance. The analysis used in this research is multiple regression analysis. Pursuant to result of research indicate that variable of organizational citizenship behavior consist of compliance, participation, and loyalty have an influence to performance of Poltabes Barelang personnel. Most dominant factor that have an effect on to Poltabes Barelang personnel performance is participation.